Uma viagem pela Manaus-Porto Velho - Thiago Oliveira Neto (Confins)
This text is the report of a trip made by the author on the Manaus-Porto Velho highway, BR-319, between December 26, 2016, and January 1, 2017. In it, we highlight the peculiarities of the trip and the space organization that the transporters have to propitiate the road trips. The structure of the text constitutes a narrative, listing relevant aspects experienced, obstacles, flows and points of support.